Cover Picture: Development of Palladium Surface‐Enriched Heteronuclear Au–Pd Nanoparticle Dehalogenation Catalysts in an Ionic Liquid (Chem. Eur. J. 4/2013). Issue 4 (15th January 2013) - Yuan, Xiao; Sun, Geng; Asakura, Hiroyuki; Tanaka, Tsunehiro; Chen, Xi; Yuan, Yuan; Laurenczy, Gabor; Kou, Yuan; Dyson, Paul J.; Yan, Ning
<x xml:space="preserve">Abstract</x> Bimetallic Au–Pd nanoparticles were prepared in the functionalized ionic liquid [C2OHmim][NTf2] by the thermal decomposition of Pd(OAc)2 and Au(OAc)3. The Au atoms are mostly located in the NP core, leaving the Pd atoms enriched at the surface. Moreover, the Pd atoms are electropositive, which leads to high activity in catalytic dehalogenation reactions. The activity of the heteronuclear nanoparticles may be attributed to charge transfer from Pd to Au and consequently to more efficient reductive elimination. For more details, see the Full Paper by N. Yan et al. on page 1227 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>